2021
DOI: 10.1590/0100-29452021022
|View full text |Cite
|
Sign up to set email alerts
|

Methods of application of indolebutyric acid and basal lesion on ‘Woodard’ blueberry cuttings in different seasons

Abstract: Blueberry cuttings are difficult to root, so alternatives that maximize their rhizogenic potential are essential for the expansion of the crop. The objective of this work was to evaluate the effect of the basal lesion and different methods of indolebutyric acid (IBA) on the rooting of ‘Woodard’ herbaceous cuttings, collected in two seasons. The experimental design used was completely randomized in a 3x2x2 factorial arrangement, totaling 12 treatments and five replications. The factors consisted of different wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…In this case, K + ions concentrate in the tissue when applying IBAand play a significant role in root initiation by dissolving the epidermal layer. However, they destroy the epidermal layer and adjacent cells when in excess instead of dissolving the epidermal layer (HIGUCHI et al, 2021). The results indicated that the use of an alcoholic solution and the IBAdose were toxic to cuttings of blueberry cv.…”
Section: Sapelli Et Almentioning
confidence: 98%
“…In this case, K + ions concentrate in the tissue when applying IBAand play a significant role in root initiation by dissolving the epidermal layer. However, they destroy the epidermal layer and adjacent cells when in excess instead of dissolving the epidermal layer (HIGUCHI et al, 2021). The results indicated that the use of an alcoholic solution and the IBAdose were toxic to cuttings of blueberry cv.…”
Section: Sapelli Et Almentioning
confidence: 98%
“…A formação de raízes adventícias é considerada um pré-requisito para a propagação do corte com sucesso a (Fonseca & Oliveira, 2007;Gaspar, 2017). Contudo, devido à arquitetura especial da raiz de mirtilo, que consiste principalmente de raízes finas, o seu cultivo requer certas condições ambientais, como umidade, permeabilidade e o pH do solo, o que torna o processo difícil, geralmente levando a uma menor porcentagem de enraizamento (Higuchi, et al, 2021).…”
Section: Introductionunclassified